Challenges and Experiences Extending the cBioPortal for Cancer Genomics to a Molecular Tumor Board Platform. - Reimer, Niklas; Unberath, Philipp; Busch, Hauke; Börries, Melanie; Metzger, Patrick; Ustjanzew, Arsenij; Renner, Christopher; Prokosch, Hans-Ulrich; Christoph, Jan (Studies in health technology and informatics, 2021)
In Molecular Tumor Boards (MTBs), therapy recommendations for cancer patients are discussed. To aid decision-making based on the patient's molecular profile, the research platform cBioPortal was extended based on users' requirements. Additionally, a comprehensive dockerized workflow was developed to support the deployment of cBioPortal and connected services. In this work, we present the challenges and experiences of nearly two years of implementing and deploying an MTB platform based on cBioPortal and compare those to findings of a previous study.
EVALuna2:512349